The Salzburg Statement on Vaccination Acceptance. Issue 5 (4th May 2019) - Ratzan, Scott C.; Bloom, Barry R.; El-Mohandes, Ayman; Fielding, Jonathan; Gostin, Lawrence O.; Hodge, James G.; Hotez, Peter; Kurth, Ann; Larson, Heidi J.; Nurse, Joanna; Omer, Saad B.; Orenstein, Walter A.; et al.
Abstract : Immunization represents one of the greatest public health achievements. Vaccines save lives, make communities more productive and strengthen health systems. They are critical to attaining the UN Sustainable Development Goals. Vaccination also represents value for investment in public health. It is undisputedly one of the most cost-effective ways of avoiding disease, each year preventing 2–3 million deaths globally. We the concerned scientists, public health professionals, physicians, and child health advocates issue this Salzburg Statement along with the International Working Group on Vaccination and Public Health Solutions, proclaiming our unwavering commitment to universal childhood vaccination, and our pledge to support the development, testing, implementation, and evaluation of new, effective, and fact-based communication programs. Our goal is to explain vaccinations to parents or caregivers, answer their questions, address their concerns, and maintain public confidence in the personal, family and community protection that childhood vaccines provide. Every effort will also be made to communicate the dangers associated with these childhood illnesses to parents and communities since this information seems to have been lost in the present-day narrative. While vaccine misinformation has led to serious declines in community vaccination rates that require immediate attention, in other communities, particularly in low-income countries, issues such as lack of access. and unstable supply of vaccines need to be addressed.